On a class of singular stochastic control problems for reflected diffusions - Giorgio Ferrari (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
Reflected diffusions naturally arise in many problems from applications ranging from economics and mathematical biology to queueing theory. In this paper we consider a class of infinite time-horizon singular stochastic control problems for a general onedimensional diffusion that is reflected at zero. We assume that exerting control leads to a state-dependent instantaneous reward, whereas reflecting the diffusion at zero gives rise to a proportional cost with constant marginal value. The aim is to maximize the total expected reward, minus the total expected cost of reflection. We show that depending on the properties of the state-dependent instantaneous reward we can have qualitatively different kinds of optimal strategies. The techniques employed are those of stochastic control and of the theory of linear diffusions.
urn:nbn:de:0070-pub-29304334
Keywords: 330; reflected one-dimensional diffusions; singular stochastic control; variational inequality; optimal stopping; optimal dividend; optimal harvesting